Stability analysis of slopes based on cloud model-Monte Carlo coupling - Han, Liwei; Chen, Ming; Sun, Zuozhuang; Si, Jiaxuan; Ma, Liyuan; Ji, Wenhui; Zhang, Hongyang (Frontiers in Earth Science, 2023)
Risk analysis of dams is essential to ensure the safety and stability of hydraulic projects. In order to improve the accuracy and reliability of risk analysis, a coupled "cloud model-Monte Carlo" model is proposed based on the cloud theory approach and a study of the distribution types of soil shear strength indicators based on indoor geotechnical test results. The cloud model is used to describe the uncertainty of risk factors and to determine the probability distribution type of shear strength parameters, while the Monte Carlo method is used to simulate the random variables in the model. The validity of the proposed model is verified by using the risk analysis of an earth dam as an example, and the results show that the model is more accurate and reliable than traditional methods. The results show that the risk probability for this dam is 9.01 x 10-6 at the design flood level, which exceeds the permissible risk criterion of 0.5 x 10-6 and must therefore be strengthened. The model proposed in this paper can accurately assess the risk of the dam and provide a scientific basis for decisions on dam safety management.